Herbicide application improved weed control and yield in Bajra Napier Hybrid - Kantwa, Sita Ram; Govindasamy, Prabhu; Palsaniya, Dana Ram; Kumar, Sunil (The Indian Journal of Agricultural Sciences, 2020)
Weeds impair the production and quality of forage crops. A research was performed to assess the PE application of oxadiargyl and sequential application of oxadiargyl PE fb 2,4-D POE for weed control, microbial and enzymatic activity, and yield in Bajra Napier hybrid (BN hybrid; Pennisetum glaucum Ã— Pennisetum purpureum). Weed density, microbial count, dehydrogenase (DHA) activity and yield data were recorded during 2015 and 2016 rainy season. The data from this study indicated dominant weed flora of the experimental site was Commelina benghalensis (13%), Echinochloa colona (28%), Cyperus rotundus (30%) and other weeds (29%). Plots treated with oxadiargyl preemergence (PE) had lower density and biomass of Echinochloa colona, Cyperus rotundus and total weeds at 25 days after planting (DAP); similar trend was also observed at 50 DAP. However, lower density of Commelina benghalensis and other weeds were recorded in oxadiargyl PE fb 2,4-D POE treated plots compared to oxadiargyl PE at 50 DAP, due to ability of 2,4-D on controlling broadleaved weeds. A similar green fodder (GF) and dry fodder (DF) yield was recorded in oxadiargyl PE and oxadiargyl PE fb 2,4-D POE. Weed control treatment evaluation indices including weed control efficiency (WCE), herbicide efficiency index (HEI) and weed index (WI) also showed no difference among herbicide treatments with respect to total weed control and crop yield. Weed management in BN hybrid either using oxadiargyl PE or oxadiargyl PE fb 2,4-D POE provide an effective weed control and better yield.